Biochemical Investigation of Oil of Elettaria cardamomum - Khan, M.R.; Haq, I. (Asian Journal of Chemistry, 2012)
The oil of cardamom was extracted with petroleum ether and ethyl alcohol. The oil was subsequently investigated for its fundamental properties and antibacterial activity. The residue of cardamomum left after extraction was checked for only antibacterial activity. It was observed that the oil extracted with petroleum ether was not active against E. coli and S. auerus, while the residue left after extraction was also inactive against E. coli and S. aureus. The oil extracted with ethyl alcohol and residue left after the extraction was also found inactive against E. coli and S. aureus. The physical and chemical properties of oils were also determined and compared. The oils extracted were also subjected to thin layer chromatography to determine the polar and non-polar lipids.